Assessing the association of common genetic variants in EPHB4 and RASA1 with phenotype severity in familial cerebral cavernous malformation. Issue 10 (7th September 2021) - Choksi, Foram; Weinsheimer, Shantel; Nelson, Jeffrey; Pawlikowska, Ludmila; Fox, Christine K.; Zafar, Atif; Mabray, Marc C.; Zabramski, Joseph; Akers, Amy; Hart, Blaine L.; Morrison, Leslie; McCulloch, Charles E.; et al.
Abstract: Background: To investigate whether common variants in EPHB4 and RASA1 are associated with cerebral cavernous malformation (CCM) disease severity phenotypes, including intracranial hemorrhage (ICH), total and large lesion counts. Methods: Familial CCM cases enrolled in the Brain Vascular Malformation Consortium were included ( n  = 338). Total lesions and large lesions (≥5 mm) were counted on MRI; clinical history of ICH at enrollment was assessed by medical records. Samples were genotyped on the Affymetrix Axiom Genome‐Wide LAT1 Human Array. We tested the association of seven common variants (three in EPHB4 and four in RASA1 ) using multivariable logistic regression for ICH (odds ratio, OR) and multivariable linear regression for total and large lesion counts (proportional increase, PI), adjusting for age, sex, and three principal components. Significance was based on Bonferroni adjustment for multiple comparisons (0.05/7 variants = 0.007). Results: EPHB4 variants were not significantly associated with CCM severity phenotypes. One RASA1 intronic variant (rs72783711 A>C) was significantly associated with ICH (OR = 1.82, 95% CI = 1.21–2.37, p  = 0.004) and nominally associated with large lesion count (PI = 1.17, 95% CI = 1.03–1.32, p  = 0.02). Conclusion: A common RASA1 variant may be associated with ICH and large lesion count in familial CCM. EPHB4 variants were not associated with any of the three CCM severity phenotypes. Abstract : We investigated whether common variants in EPHB4 and RASA1 are associated with familial cerebral cavernous malformation (CCM) disease severity phenotypes, including intracranial hemorrhage (ICH), total and large lesion counts. EPHB4 variants were not associated with any of the three CCM severity phenotypes. However, an intronic RASA1 variant was significantly associated with ICH and large lesion count in familial CCM, suggesting that the Ras‐Erk pathway may play a role in CCM disease severity.